O cuidado fisioterapêutico a pacientes idosos hospitalizados: um convite ao olhar fisiogerontológico - Soares, Elizabeth Viana (2008)
Ageing and become old is not an easy path, and, set these terms, it depends on the conceptions of individual and cultural concepts of society. During the ageing several changes occur through physical changes, emotional, social, and economic. These changes, particularly those related to organic part of the body, are responsible for the large outbreak of diseases in old age. The complications of the disease at this stage can be considered as the cause for hospitalization of these subjects. The period of hospitalization is regarded as a moment where various procedures are carried out and responsible for great moments of stress for these patients. This stress can be fought during hospitalization is the treatment of diseases of Caring comes together. This study aimed to ascertain whether there is proposed the creation of the act of care from physiotherapists, in addition to know what the definitions of old, old age and aging for these professionals. To achieve this, the research work was developed based on qualitative kind of semi-structured interviews with 13 physiotherapists who exercise their duties in Hospital Ferreira Machado, located in Campos dos Goytacazes / RJ. The results of this research showed that despite the professional show different opinions related to ageing, as only physical changes, they make the care and treat hand together